If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 4 = -5x + -66 Reorder the terms: 4 + 5x = -5x + -66 Reorder the terms: 4 + 5x = -66 + -5x Solving 4 + 5x = -66 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 4 + 5x + 5x = -66 + -5x + 5x Combine like terms: 5x + 5x = 10x 4 + 10x = -66 + -5x + 5x Combine like terms: -5x + 5x = 0 4 + 10x = -66 + 0 4 + 10x = -66 Add '-4' to each side of the equation. 4 + -4 + 10x = -66 + -4 Combine like terms: 4 + -4 = 0 0 + 10x = -66 + -4 10x = -66 + -4 Combine like terms: -66 + -4 = -70 10x = -70 Divide each side by '10'. x = -7 Simplifying x = -7
| (4-y)(-9)= | | 2(1-2n)-4=10 | | -4b=100 | | 5w^2=400 | | r+2s+3r= | | 5x^2+7=7.8 | | 5a-2(4a+5)=7a | | 15y-6y^2=0 | | y-11=-16 | | 20-(8+x)=-(1-x)+29 | | X+(x-30)=190 | | t-1=-3 | | 5x+15=3x+19 | | 6y-9+10y= | | 27=3c-3(6-6c) | | -2(1-2k)-4=-10 | | 3705=y^2+436 | | 7=3c-3(6-2c) | | -6k=-42 | | -38-4= | | 3x-8=7x+5 | | 5-9=-17 | | -8(1+6n)=-8 | | 4x+3=9x+7 | | 99-2b=-1 | | 3x-2y=11 | | -6x-4x=20 | | 5(x-3)=-3x+41 | | -5x-3=-2x+8 | | 10=14+4x | | x+4=3x-2-6 | | 10+3(x-2)=31 |